Proses Pembentukan Kata dalam Kumpulan Cerpen Cinta Paling Rumit Karya Boy Candra - Putri, Intan Peonnyta Oktaviani; Simpen, I Wayan; N. Widarsini, Ni Putu (Humanis; Vol 23 No 2 (2019), 2019)
This research “The Process of Forming Words in Short Story Collection Cinta Paling Rumit Karya By Candra” The purpose of this research was to know the formation of words which is affixation, reduplication, and composition in the short story collection Cinta Paling Rumit by Boy Candra. The theory used in this research is morphological theory. The methods and techniques used in the process of the collecting the data are the method of reffering to tapping techniques, proficient non-invulment listening techniques, and note-taking techniques. Then in analyzing data, the methods and techniques used are the agih methods with the direct elements technique, the advanced techniques used are sloping techniques, the substitution techniques, and repetition techniques. Besides using the agih method in process of analyzing data, this research also uses quantitative methods. Meanwile, the method of presenting the results data analysis uses informal methods and formal methods. In this research found affixation, the reduplication, and composition. The affixation found were 681 words (31%), reduplication found were 150 words (7%), and the composition found were 93 word (4%).